EVALUASI PELAKSANAAN PELATIHAN PELAYANAN TERPADU SATU PINTU SECARA DARING TAHUN 2021 - Abdul Kholik; Helena Ras Ulina Sembiring (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
One Stop Service (e.g PTSP) is one of the government programs to provide fast, easy, cheap, transparent, sure and affordable services. One of the determinants of the success of PTSP in service is human resources in mastering the technical licensing process. To meet these needs, in 2021 the DKI Jakarta BPSDM will conduct online PTSP Training to anticipate the Covid-19 pandemic. In order to realize good training, it is necessary to evaluate to get input for the development of further training programs. The evaluation was carried out using the CIPP (Context – Input – Process – Product) evaluative model. The results show that in general the PTSP 2021 online training has not been carried out effectively, both in terms of context, input, process and product. The participants felt that this training was very useful, so it needed to be continued with improvements, and it was recommended to use blended learning.